Bi-stable electronic states of cobalt phthalocyanine molecules on two-dimensional vanadium diselenide. (March 2020) - Zhang, Lei; Yang, Tong; Zhang, Wen; Qi, Dongchen; He, Xiaoyue; Xing, Kaijian; Wong, Ping Kwan Johnny; Feng, Yuan Ping; Wee, Andrew Thye Shen
Graphical abstract: Abstract: Hybrid organic/2D interfaces combine the wide spectrum of 2D material properties with the major advantages of organic materials, such as low cost, mechanical flexibility, and chemical tunability. Here, we report the electronic properties of cobalt phthalocyanine (CoPc) molecules adsorbed on molecular beam epitaxy-grown monolayer vanadium diselenide (VSe2 ). Using scanning tunneling microscopy/spectroscopy, we provide evidence of highly ordered molecular assembly on monolayer VSe2, with two distinctive bright and regular molecular contrasts, which are not observed on graphite. These contrasts also lead to a distinct difference in the electronic state of the molecule's central Co atom, for which density functional theory calculations indicate the regular state as the ground state. A correlation between these two molecular states and the charged states of individual molecules is postulated, as demonstrated by the possibility of switching the bright state to the regular state using a negative tip voltage pulse.